1948
DOI: 10.1021/ja01190a007
|View full text |Cite
|
Sign up to set email alerts
|

Naphthoquinone Antimalarials. XIV. 2-Hydroxy-3-aryl-1,4-naphthoquinones

Abstract: The observation1 that 2-hydroxy-3-phenyl-1,4-naphthoquinone2 (IV, Ri = R.2 = Rs = H) has an activity approximately one-fourth that of quinine against P. lophurae in ducks, prompted further investigation in this series.It was decided to diversify the method used by Volhard2 in the preparation of the parent compound, by starting with various substituted phenylacetic esters (I). In this way nine new

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1957
1957
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The synthesis of the derivatives in the second group (8)(9)(10)(11)(12)(13)(14)(15)(16) with the pyridinylamino or dibenzylamino groups on their side chains is shown in Chart 2. Specifically, 4-methyl-2-aminopyridine and dibenzylamine were used as aromatic amines in the Mannich reaction.…”
Section: Chemical and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the derivatives in the second group (8)(9)(10)(11)(12)(13)(14)(15)(16) with the pyridinylamino or dibenzylamino groups on their side chains is shown in Chart 2. Specifically, 4-methyl-2-aminopyridine and dibenzylamine were used as aromatic amines in the Mannich reaction.…”
Section: Chemical and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…During the last 50 years, various naphthoquinones and especially lawsone derivatives have been designed and extensively synthesized for the development of novel antiparasitics. [11][12][13][14] Within these studies, the 1,4-naphthoquinone analogues have been found to possess not only antimalarial activity but also a diverse range of biological activities, such as antioxidant, antibacterial, antitumor, antituberculosis activities. [14][15][16][17][18] Aminonaphthoquinone belongs to the quinone family which possesses an interesting scaffold conveying potential for a range of pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the base of choice, potassium carbonate was selected for several reasons, including cost-effectiveness and safety in large-scale reactions. Moreover, most 2-hydroxynaphthoquinones (for example, phthiocol: pK a 5.08 17 and lawsone: pK a 3.98 18 ) are weak acids that can be easily deprotonated in the presence of mild carbonate salts. We also assumed that ion pairing with potassium cations would be effectively suppressed by the 18-crown-6 ether, impeding formation of metal complexes such as 1.…”
mentioning
confidence: 99%
“…Other 2-hydroxynaphthoquinones were evaluated to assess the effects of substituents on the O-alkylation reaction ( Table 1, entries 14-21). Moderate yields (44-59%) were obtained for the benzyl-, anisyl-, and chloro-substituted quinones 3l-p (entries [16][17][18][19][20]. However, when an electron-donating substituent (cyclohexyl) was present, the isolated yields rose to 72-82% (entries 14 and 15).…”
mentioning
confidence: 99%
See 1 more Smart Citation